ANALISIS HUKUM PENYELESAIAN SENGKETA PENGAMANAN JALAN DALAM MASYARAKAT TERHADAP TRUK - Siagian, Pangeran Goklas Jeremia; Sidauruk, Jinner (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
The resolution regarding protecting roads in the community against trucks, especially in the context of coal transportation in Jambi Province, is a complex legal issue. The increasing volume of heavy vehicles, especially trucks carrying coal, causes road damage, severe traffic jams and accidents that are detrimental to the community. Legal protection for road users, especially those affected by coal transportation activities, needs to be considered to reduce the risk of accidents and material loss. This research aims to analyze the legal arrangements for resolving road disputes, as well as the resolution mechanisms available in Indonesia. The research results show that although there are regional regulations governing the transportation of coal, the implementation of these regulations is not optimal. Law enforcement and supervision of coal transportation as well as setting truck operating schedules are very important to improve the safety and comfort of road users.